Category viability: balanced levels of coherence and distinctiveness - Lo,JY-C; Rhee,E; Fiss,P; Kennedy,MT (Academy of Management Review, 2020)
In a growing body of literature on categorization in organization theory, researchers are exploring the stabilizing role of categories and the processes by which they emerge. Because the literature focuses mainly on categories that emerge successfully or are already established, we know much less about why categories fall out of use or fail to emerge. Rather than viewing declining usage or failed emergence as different processes, we argue that they are two aspects of the single problem of understanding what makes a category viable. Focusing on the coherence of the items included in a category and how distinct they are compared to items in other categories, we develop the concept of category viability and argue that viable categories are those found useful for sensemaking, analysis, and coordination because they balance both coherence and distinctiveness to fall within what we call a zone of viability. To illustrate how category viability helps explain both change and continuity of categories, we also offer a framework to describe the process by which categories move in or out of the zone of viability with deliberate actions or with shifting circumstances that change their members or positions relative to other categories.